Belly button piercings: a saving grace? A patent urachus presenting in a 17-year-old girl. (10th June 2014) - Bannon, Aidan; Black, Patrick; Turner, Joanna; Gray, Sam; Kirk, Stephen
Abstract : We report the case of a 17-year-old girl who presented to the accident and emergency department with dysuria and foul smelling, bloody discharge from her umbilicus. The definitive diagnosis was that of a patent urachus, which is a fistulous communication between the bladder and the umbilicus, usually diagnosed in early infancy. The incidence of a patent urachus is approximately 1 in 70 000 in the general population. It is highly likely that removal of a recent belly button piercing resulted in the acute presentation by completing the fistulous tract to the skin. This case is of clinical relevance as the diagnosis was missed 18 months prior with a milder presentation. The recommended treatment option is surgical excision due to the potential risk of malignant change, with urachal adenocarcinoma accounting for 0.3% of all bladder cancers.